2015
DOI: 10.1155/2016/6929306
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation Effect of Simvastatin in Aorta and Hippocampus: A Rabbit Model Fed High‐Cholesterol Diet

Abstract: We show that hypercholesterolemia contributes to oxidative stress injury progression in brain and simvastatin counteracts the cholesterol-induced peroxidation injury in rabbit hippocampus, and we demonstrate for the first time that the simvastatin is a critical role in brain protection and identify HO-1 and other related antioxidant enzymes as molecular target for active redox compounds. Second, our experiments have pointed out an association between statin treatment and a decrease in the risk of having peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(51 reference statements)
0
9
0
Order By: Relevance
“…The HFD administered to our rabbits enhances lipid oxidation. This is indicated by MDA rise according to Yu et al [ 55 ], Zhang et al [ 65 ], Sethi et al [ 63 ], Apaijai et al [ 66 ], and Pipatpiboon et al [ 67 ]. It also minimizes the total antioxidant protection by AOA and ascorbic acid level reduction as in the study of Moor de Burgos et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HFD administered to our rabbits enhances lipid oxidation. This is indicated by MDA rise according to Yu et al [ 55 ], Zhang et al [ 65 ], Sethi et al [ 63 ], Apaijai et al [ 66 ], and Pipatpiboon et al [ 67 ]. It also minimizes the total antioxidant protection by AOA and ascorbic acid level reduction as in the study of Moor de Burgos et al [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerotic cardiovascular disease is a major cause of morbidity and mortality worldwide [1]. Hypercholesterolaemia has been shown to be a major risk factor for atherosclerosis, associated with increasing oxidative stress and impaired endothelial function [2, 3]. The normal endothelium plays an important role in maintaining vascular homeostasis and regulating basal vascular tone through the production of several vasoactive substances, including nitric oxide (NO) and endothelin [4].…”
Section: Introductionmentioning
confidence: 99%
“…The previous data reported that that simvastatin improved the antioxidant status via prevention of oxidative stress 56 . Also, Zhang et al 2016 57 indicated statins reversed the increase in lipid peroxidation the decrease in GSH-Px expression in the hippocampus hypercholesterolemic rabbits compared to the control group. Moreinga oleifera extract has been shown to decrease immobility duration, as well as a reduction in blood MDA 58 .…”
Section: Discussionmentioning
confidence: 98%